2008
DOI: 10.1302/0301-620x.90b6.19805
|View full text |Cite
|
Sign up to set email alerts
|

Limb-sparing surgery preserves more function than amputation

Abstract: We evaluated the long-term functional outcome in 118 patients treated for osteosarcoma or Ewing's sarcoma in the extremities a minimum of five years after treatment. We also examined if impaired function influenced their quality of life and ability to work. The function was evaluated according to the Musculoskeletal Tumor Society (MSTS) score and the Toronto Extremity Salvage Score (TESS). Quality of life was assessed by using the Short Form-36 (SF-36). The mean age at follow-up was 31 years (15 to 57) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(95 citation statements)
references
References 44 publications
(63 reference statements)
5
79
1
5
Order By: Relevance
“…We found that the LSS is better than amputation in functional outcomes, which are consistent with other studies [26, 27]. Johansen et al [28] had reported notably higher functional scores after LSS compared with amputation respectively ( P  = 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the LSS is better than amputation in functional outcomes, which are consistent with other studies [26, 27]. Johansen et al [28] had reported notably higher functional scores after LSS compared with amputation respectively ( P  = 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…3C and D). In accordance with the results from the present study, previous studies have demonstrated that the functional outcomes of epiphysis preservation surgery are similar to those of other limb-saving techniques (22,23). …”
Section: Discussionsupporting
confidence: 92%
“…The Toronto Extremity Salvage Score (TESS) is an extremity-tumour-specific self-report measure of disability secondary to activity limitation [10]. Ease of completion of 29-30 everyday activities is assessed via a 5-point Likert scale with the option of indicating whether the specific task is not applicable to the respondent.…”
Section: Methodsmentioning
confidence: 99%
“…Previous early studies exploring psychological distress and QoL in ES patients tended to be limited to cross-sectional, retrospective studies of survivors [410]. Most had small numbers of participants and few were prospectively designed with a baseline measure of QoL and mental health or controlled for the context of the timepoint of the cancer journey [1115].…”
Section: Introductionmentioning
confidence: 99%